When there are no good choices: illuminating the borderland between proportionate palliative sedation and palliative sedation to unconsciousness. (January 2011) - Reid, Thomas T; Demme, Richard A; Quill, Timothy E
Background: Despite state-of-the-art palliative care, some patients will require proportionate palliative sedation as a last-resort option to relieve intolerable suffering at the end of life. In this practice, progressively increasing amounts of sedation are provided until the target suffering is sufficiently relieved. Uncertainty and debate arise when this practice approaches palliative sedation to unconsciousness (PSU), especially when unconsciousness is specifically intended or when the target symptoms are more existential than physical.Methods: We constructed a case series designed to highlight some of the common approaches and challenges associated with PSU and the more aggressive end of the spectrum of proportionate palliative sedation as retrospectively identified by palliative care consultants over the past 5 years from a busy inpatient palliative care service at a tertiary medical center in Rochester (NY, USA).Results: Ten cases were identified as challenging by the palliative care attendings, of which four were selected for presentation for illustrative purposes because they touched on central issues including loss of capacity, the role of existential suffering, the complexity of clinical intention, the role of an institutional policy and use of anesthetics as sedative agents. Two other cases were selected focusing on responses to two special situations: a request for PSU that was rejected; and anticipatory planning for total sedation in the future.Conclusion: Although relatively rare, PSU and more aggressive end-of-the-spectrum proportionate palliative sedation represent responses to some of the most challenging cases faced by palliative care clinicians. These complex cases clearly require open communication and collaboration among caregivers, patients and family. Knowing how to identify these circumstances, and how to approach these interventions of last resort are critical skills for practitioners who take care of patients at the end of life.